2010
DOI: 10.1007/s00586-010-1662-9
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cell co-culture modulates the immunological properties of human intervertebral disc tissue fragments in vitro

Abstract: The capacity of mesenchymal stem cells (MSCs) to differentiate into intervertebral disc (IVD)-like cells has been well described, but their ability to modulate the inflammatory processes in the IVD remains unclear. We found that tissue obtained by discectomy of degenerated and post-traumatic IVD contains significant amounts of IgG antibodies, a sign of lymphocyte infiltration. Further we investigated whether MSCs in vitro, which were characterized for their multilineage differentiation potential and may have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…One of these includes time in culture to guarantee tissue viability (usually up to 1 week) [39][40][41]. Here, tissue viability maintenance was monitored by mitochondrial metabolic activity and DNA content.…”
Section: Discussionmentioning
confidence: 99%
“…One of these includes time in culture to guarantee tissue viability (usually up to 1 week) [39][40][41]. Here, tissue viability maintenance was monitored by mitochondrial metabolic activity and DNA content.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study we have detected IgG antibodies in human degenerated and post-traumatic disc fragments S Capossela et al Autoantibodies in human intervertebral discs cultured in vitro (Bertolo et al, 2011), but we did not identify their targets. Based on the above mentioned data and studies, we put to test the hypothesis that if the integrity of vertebral endplates is compromised by trauma or degeneration, antibodies against disc proteins would be present locally.…”
Section: S Capossela Et Almentioning
confidence: 95%
“…Deposits of immunoglobulin G and M in human disc herniated tissue suggests a correlation between inflammation and autoimmune response (Habtemariam et al, 1996). Furthermore, we have recently shown that significant amounts of IgG antibodies remain in human degenerated and post-traumatic IVDs, despite thorough washing after discectomy (Bertolo et al, 2011). Until now however, there are no studies in humans, which show the specificity of the antibodies present in the disc.…”
Section: Introductionmentioning
confidence: 91%
“…Several tissue engineering (TE) protocols of the disc have been developed, and the use of mesenchymal cells (MSC) has been shown to be promising, but MSC introduction in the degenerate tissue should be accurately designed using TE strategies, because some adverse effects have been reported [8,9]. This study is the first part of an investigation on the tissue features of IVD retrievals, and ability of disc cell to expand in vitro.…”
Section: Introductionmentioning
confidence: 99%